The concentration of chemicals in paddy planting in Kg Wang Ulu, Perlis - Siti Sarah Binti Sofi (School of Environmental Engineering Universiti Malaysia Perlis, 2011)
Paddy is essentially important in our part of daily life. The production of paddy in Malaysia was inceased every year as the population increased. Perlis is one of the states that produces paddy because a lot of the swampy area in Perlis. This research actually concern about the concentration of chemicals that presented in water paddy panting area. The concentration of chemicals is due to the fertilizer and pesticides been used during the paddy planting process thet will flow out to the surrounding area such as canal, lakes, and rivers. Hence, the concentration of chemicals in the water will effect the quality of water. The method used to determine the concentration of chemicals is standard methods for most of parameters in this research.